2018
DOI: 10.1016/s1470-2045(17)30900-2
|View full text |Cite|
|
Sign up to set email alerts
|

Avelumab in metastatic urothelial carcinoma after platinum failure (JAVELIN Solid Tumor): pooled results from two expansion cohorts of an open-label, phase 1 trial

Abstract: Merck KGaA, and Pfizer Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
390
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(404 citation statements)
references
References 31 publications
7
390
0
7
Order By: Relevance
“…Confirmed ORR was 17%, including 6% CR, 11% partial response (PR), and median OS 6.5 months. This ORR was observed (24%) in the high PD-L1 expression group (defined in this study as ≥5% staining of tumor cells only) [28]. Safety profiles showed a low rate of grade 3 to 4 TRAEs (8%) and no treatment-related deaths.…”
Section: Immune Checkpoint Inhibitors After Platinum-based Chemotheramentioning
confidence: 65%
See 1 more Smart Citation
“…Confirmed ORR was 17%, including 6% CR, 11% partial response (PR), and median OS 6.5 months. This ORR was observed (24%) in the high PD-L1 expression group (defined in this study as ≥5% staining of tumor cells only) [28]. Safety profiles showed a low rate of grade 3 to 4 TRAEs (8%) and no treatment-related deaths.…”
Section: Immune Checkpoint Inhibitors After Platinum-based Chemotheramentioning
confidence: 65%
“…In a phase Ib trial, avelumab showed clinical efficacy in patients with platinum-refractory mUC (JAVELIN Solid Tumor trial, NCT01772004) [28]. Confirmed ORR was 17%, including 6% CR, 11% partial response (PR), and median OS 6.5 months.…”
Section: Immune Checkpoint Inhibitors After Platinum-based Chemotheramentioning
confidence: 99%
“…Avelumab, an anti‐PD‐L1 antibody, received accelerated FDA approval for UC patients in the second‐line setting after platinum‐based chemotherapy. The approval was based on the data from the open‐label, single‐arm, phase I dose‐expansion JAVERIN Solid Tumor study . The study analyzed 249 UC patients who had experienced progression after at least one previous platinum‐based chemotherapy or who were cisplatin‐ineligible patients.…”
Section: Immunotherapy In Ucmentioning
confidence: 99%
“…Severe AEs (grade 3–4) and grade 3–4 immune-mediated AEs occurred in 6.8 and 2.1% of the patients, respectively[11]AvelumabBavencioPD-L110 mg/kg, every 2 weeks1JAVELIN161The ORR was 17% including 6% with CR. Severe (grade 3–4) treatment-related AEs occurred in 8%[12] PD-1 programmed death 1 , PD-L1 programmed death ligand 1, OS overall survival, ORR objective response rate, CR complete response, AE adverse event, Reference the reference number in this review article …”
Section: Introductionmentioning
confidence: 99%
“…The most frequent AEs (of any grade in ≥ 10% patients) were infusion-related reaction (29%, all grade 1–2) and fatigue (16%). Severe (grade 3–4) treatment-related AEs occurred in 8%; the most common of these were fatigue (2%) and asthenia, elevated lipase, hypophosphatemia, and pneumonitis (1%) [12]. It is worth remembering that avelumab causes infusion-related reactions frequently, whereas this is seldom seen in the other checkpoint inhibitors.…”
Section: Introductionmentioning
confidence: 99%